2018
DOI: 10.48550/arxiv.1807.00547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Realisation of groups as automorphism groups in categories

Gareth A. Jones

Abstract: It is shown that in various categories, including many consisting of maps or hypermaps, oriented or unoriented, of a given hyperbolic type, every countable group A is isomorphic to the automorphism group of uncountably many non-isomorphic objects, infinitely many of them finite if A is finite. In particular, the latter applies to dessins d'enfants, regarded as finite oriented hypermaps. The proof, involving maximal subgroups of various triangle groups, yields a simple construction of a regular map whose automo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…5 This proof of Greenberg's Theorem is adapted from a proof in [10,Theorem 3(a)] that for any hyperbolic triple (l, m, n) there are ℵ 0 non-isomorphic dessins of type (l, m, n) with a given finite automorphism group A. (See also [9] for related results by Hidalgo on realising groups as automorphism groups of dessins.)…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This proof of Greenberg's Theorem is adapted from a proof in [10,Theorem 3(a)] that for any hyperbolic triple (l, m, n) there are ℵ 0 non-isomorphic dessins of type (l, m, n) with a given finite automorphism group A. (See also [9] for related results by Hidalgo on realising groups as automorphism groups of dessins.)…”
Section: Remarksmentioning
confidence: 99%
“…Again, the proof is rather delicate (but see [1] for a more elementary geometric proof). In [10] it is shown that for many hyperbolic triples (including all of non-cocompact type and many of cocompact type), every countable group can be realised as the automorphism group of 2 ℵ 0 non-isomorphic oriented hypermaps of that type. It would be interesting to try to deduce Greenberg's result for countable groups from this.…”
Section: Remarksmentioning
confidence: 99%
“…Soon after a draft of this paper appeared on the arXiv, the authors were notified by Gareth A. Jones that his paper [12] contains similar results for a wider class of group. In particular, by [12,Theorem 3], all hyperbolic (extended) triangle groups are shown to be "finitely abundant", which is equivalent to being telescopic for the non-compact ones among them. Also, all subgroups produced in [12,Theorem 3] are, in fact, torsion-free.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, by [12,Theorem 3], all hyperbolic (extended) triangle groups are shown to be "finitely abundant", which is equivalent to being telescopic for the non-compact ones among them. Also, all subgroups produced in [12,Theorem 3] are, in fact, torsion-free. The methods used in [12] and in our paper differ substantially, as well as the emphasis in our work is on the quantitative aspects, such as counting of combinatorial objects with given symmetries.…”
Section: Introductionmentioning
confidence: 99%
“…The question whether or not a given group is the automorphism group or symmetry group of a geometric, combinatorial, algebraic, or topological structure of a specified kind has been studied quite extensively. For a recent article describing the common characteristics of the approaches see the recent article [Jon18] by Jones.…”
Section: Introductionmentioning
confidence: 99%